The six-stage model of profitable growth and entrepreneurship in Finland: a Delphi study - Myllylä, Yrjö; Kaivo-oja, Jari (Journal of Business Economics and Management, 2025)
Our research has focused on addressing the following research questions for the growth strategies of SMEs: (1) What are the stages of profitable growth, and what factors contribute to these growth stages? (2) Which critical factors must be addressed for an organization to progress to the next stages of growth? (3) What is the importance of management in identifying and addressing critical growth factors? We have utilized the Delphi method and emphasized the role of company managers who have experienced profitable growth process as experts. Based on our findings, we have developed a Six-Stage Model of Profitable Growth (SSMPG), which we explain in detail in the article. The SSMPG model is compared to the prevailing Death Valley and Startup growth company development models. The article identifies the most crucial factors for the profitable growth of SMEs at different stages of growth within the SSMPG model. This model emphasizes sales, profitability, the individual characteristics of the entrepreneur, and leadership, in contrast to the debt-driven growth models emphasized in the other approaches. Further research could explore developing a start-up business culture using the new phasing model in Europe and elsewhere. In the future, it is important to consider profitability at both the company level and within clusters and regions.